2015
DOI: 10.11138/fneur/2015.30.1.053
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three different jaw positions on postural stability during standing

Abstract: SummaryStudies in the literature show that jaw and neck regions are linked anatomically, biomechanically and neurologically. Voluntary clenching has been shown to improve muscle strength and performance of various motor tasks. Information from the neck sensory-motor system is reported to be important for posture. Hence it is reasonable to believe that activation of the jaw sensorymotor system has the potential to modulate posture. In a sample of 116 healthy subjects, we compared center of gravity (COG) velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
(60 reference statements)
0
6
0
1
Order By: Relevance
“…Concerning occlusal strength, certain studies described that spinal excitability is enhanced with increasing occlusal strength 16–18 . Our research group also investigated teeth occlusion with low‐to‐high intensity and revealed a correlation between spinal cord excitability and occlusal strength 19 In addition, in line with enhanced spinal cord excitability, muscle strength would be activated immediately 7,19–22 . However, we described in our previous research that spinal reciprocal inhibition (RI), a key function in smooth joint movement, has been completely nonfunctional during high‐intensity occlusion (>50% of maximum voluntary contraction [MVC] of the masseter muscle) 19 .…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Concerning occlusal strength, certain studies described that spinal excitability is enhanced with increasing occlusal strength 16–18 . Our research group also investigated teeth occlusion with low‐to‐high intensity and revealed a correlation between spinal cord excitability and occlusal strength 19 In addition, in line with enhanced spinal cord excitability, muscle strength would be activated immediately 7,19–22 . However, we described in our previous research that spinal reciprocal inhibition (RI), a key function in smooth joint movement, has been completely nonfunctional during high‐intensity occlusion (>50% of maximum voluntary contraction [MVC] of the masseter muscle) 19 .…”
Section: Introductionmentioning
confidence: 91%
“…These studies suggest that low‐intensity occlusion (<50% MVC) could be effective in smooth joint movements due to enhanced spinal excitability and sufficient RI while high‐intensity occlusion (>50% MVC) might exert effective performance with fixed joints due to enhanced spinal excitability and RI deficit, triggering concurrent activations of both the agonist and antagonist muscles. In fact, previous experiments examining the remote facilitation from maximum effort (high‐intensity) occlusion demonstrated effective results in static standing balance stability 20–24 . However, previous studies assessing motor function with teeth occlusion have only examined high‐intensity conditions, more detailed studies including low‐intensity occlusion would thus be required.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintaining a poor head position for a long time due to excessive use of computers and smartphones in offices and homes leads to changes in the length of the anterior and posterior neck muscles and to musculoskeletal dysfunction due to constant loading on the cervical spine [ 15 ]. This condition may reversely cause jaw, neck and shoulder pain and may also indirectly affect joint position sense and postural stability [ 16 ]. Functional jaw movements involve the simultaneous mandibular and head-neck movements, which occur by activating the jaw and neck muscles in tandem.…”
Section: Introductionmentioning
confidence: 99%